GIA: A Reusable General Interposer Architecture for Agile Chiplet Integration - Li, Fuping; Wang, Ying; Cheng, Yuanqing; Wang, Yujie; Han, Yinhe; Li, Huawei; Li, Xiaowei (2022 IEEE/ACM International Conference On Computer Aided Design (ICCAD), 2022)
2.5D chiplet technology is gaining popularity for the eﬃciency of integrating multiple heterogeneous dies or chiplets on interposers, and it is also considered an ideal option for agile silicon system design by mitigating the huge design, verification, and manufacturing overhead of monolithic SoCs. Although it significantly reduces development costs by chiplet reuse, the design and fabrication of interposers also introduce additional high non-recurring engineering (NRE) costs and development cycles which might be prohibitive for application-specific designs having low volume.To address this challenge, in this paper, we propose a reusable general interposer architecture (GIA) to amortize NRE costs and accelerate integration flows of interposers across different chiplet-based systems effectively. The proposed assembly-time configurable interposer architecture covers both active interposers and passive interposers considering diverse applications of 2.5D systems. The agile interposer integration is also facilitated by a novel end-to-end design automation framework to generate optimal system assembly configurations including the selection of chiplets, inter-chiplet network configuration, placement of chiplets, and mapping on GIA, which are specialized for the given target workload. The experimental results show that our proposed active GIA and passive GIA achieve 3.15x and 60.92x performance boost with 2.57x and 2.99x power saving over baselines respectively.